Preservation Obscures Pelagic Deep-Sea Fish Diversity: Doubling the Number of Sole-Bearing Opisthoproctids and Resurrection of the Genus Monacoa (Opisthoproctidae, Argentiniformes) - Poulsen, Jan Yde; Sado, Tetsuya; Hahn, Christoph; Byrkjedal, Ingvar; Moku, Masatoshi; Miya, Masaki (PLOS ONE, 2016)
The family Opisthoproctidae (barreleyes) constitutes one of the most peculiar looking and unknown deep-sea fish groups in terms of taxonomy and specialized adaptations. All the species in the family are united by the possession of tubular eyes, with one distinct lineage exhibiting also drastic shortening of the body. Two new species of the mesopelagic opisthoproctid mirrorbelly genus Monacoa are described based on pigmentation patterns of the “sole”—a unique vertebrate structure used in the reflection and control of bioluminescence in most short-bodied forms. Different pigmentation patterns of the soles, previously noted as intraspecific variations based on preserved specimens, are here shown species-specific and likely used for communication in addition to counter-illumination of down-welling sunlight. The genus Monacoa is resurrected from Opisthoproctus based on extensive morphological synaphomorphies pertaining to the anal fin and snout. Doubling the species diversity within sole-bearing opisthoproctids, including recognition of two genera, is unambiguously supported by mitogenomic DNA sequence data. Regular fixation with formalin and alcohol preservation is shown problematic concerning the retention of species-specific pigmentation patterns. Examination or photos of fresh material before formalin fixation is shown paramount for correct species recognition of sole-bearing opisthoproctids—a relatively unknown issue concerning species diversity in the deep-sea pelagic realm.